The Positive Politeness Strategies Found In Ferdinand Movie 2017 - Sahry, Firza Fadila; Seri Malini, Ni Luh Nyoman; Sumaryana Putra, I Komang (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 29 No 2 (2022): September, 2022)
This study aimed to identify and analyse the positive politeness strategies based on Brown and Levinson(1987) politeness theory and the positive politeness according to positive politeness strategies theory by Brown and Levinson (1987:103-129) in the Ferdinand movie. This study used the descriptive-qualitative method to analyse the data and the documentation method applied to collect the data. Based on the results of the study, it can be concluded that there were 21 data found in Ferdinand movie with strategy 3 Intensify Interest To H (1 data), strategy 4 Use In-Group Identify Markers (6 data), strategy 5 Seek Agreement (2 data), strategy 6 Avoid Disagreement (1 data), strategy 10 offer, promise (1 data), strategy 12 (1 data), strategy 12 Include Both S and H in The Activity (1 data), strategy 13 Give (Or Ask for) Reasons (2 data) and strategy 15 Give Gifts to H (Goods, Sympathy, Understanding, Cooperation) (3 data)